SCARING INTEREST IN LEARNING CHEMISTRY BASED ON CAREER INTEREST THROUGH ECOLECTROCHEMISTRY: PRESENTING INCLUSIVE CHEMISTRY IN ONLINE CLASS - Zulfah Zulfah; Benny Yodi (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
The online learning of organic chemistry series chemistry in class XII MIPA Catholic SMA Santu Petrus Pontianak in the first three months of the odd semester showed a decrease in interest in learning chemistry. This study was conducted to find chemistry lessons that match the career interests of students, especially the study topics in the physical chemistry learning series (voltaic cells and electrolytic cells). On the topic of voltaic cells, group projects are carried out by choosing their own types of assignments according to the interests and learning styles of students with activities of making chemical songs, simple practicum, limited webinars and advertisements for voltaic cell products. On the topic of electrolysis cells, a group project was carried out with the concept of combining economics/business into electrochemistry, called ecolectrochemistry. The voltaic cell project assessment uses five parameters: the accuracy of the voltaic cell concept, the relevance of the voltaic cell concept to the concept raised, creativity, fulfillment of task requirements, and collaboration. The ecolectrochemistry project assesses problem-solving skills using the IDEALS model, presentation assessment and assessment of creative and disciplined attitudes. The active and enthusiastic involvement of students is better than in the organic chemistry series. There is an increase in interest in learning chemistry from 27.38% to 65.48% and there is an increase in the average learning outcomes of the physical chemistry learning series compared to the organic chemistry learning series. These results indicate that learning designed according to students'.